Perbandingan Mutu Beton terhadap Gaya Geser dan Simpangan pada Bangunan Rutan Kejati - Ahadina, Anak Agung Ananda Surya Ayugde; Sarassantika, I Putu Ellsa; Triswandana, I Wayan Gde Erick; Aryastana, Putu (Universitas Ibn Khaldun, 2025)
This study examines the planning of high-rise building structures in Indonesia, focusing on the application of Special Moment Resisting Frame (SMRF) systems under seismic conditions. Situated within the Pacific Ring of Fire, Indonesia frequently experiences significant earthquakes due to the convergence of three continental plates. Previous research indicates that the design of high-rise buildings necessitates careful attention to dimensions and reinforcement to ensure structural strength and stability. The SMRF planning method, which applies the principle of strong column weak beam, has been analyzed across various case studies, including designs for office buildings, hotels, laboratories, and educational facilities.Furthermore, this study compares the structural performance using different concrete strengths, specifically 41.5 Mpa and 24.9 Mpa, in the construction of prison walling at the Kejati Detention Center. Through quantitative analysis and structural modeling using ETABS V.20 software, this research identifies differences in base shear and inter-story drift between the two concrete strengths. The findings provide insights into the effectiveness of higher-grade concrete usage and its potential impacts on the strength and structural quality of buildings. The implications of this research can guide practitioners in selecting the appropriate construction materials to enhance performance and cost-efficiency in high-rise building projects in Indonesia.